Does The Service Quality Of Banquet Hall Staff Affect The Guest Satisfaction? A Case Study At Hotel Peninsula Manado - Kalele, Selvy; Watung, Enrico Aldo; Kondoj, Telly H. I.; Sendow, Deby Christiani; Permana, Dimas E.; Solang, Jeanlly A.; Towoliu, Benny Irwan (Faculty of Economics and Business, University of Mataram, 2025)
This study aims to examine the effect of service quality provided by staff in the banquet hall on guest satisfaction in organizing events at the Peninsula Hotel Manado. Based on the findings of researchers, every time there is an event, staff often get complaints against the organizer, and it has become a hot issue developing outside the hotel, but it is still in the local Manado context. However, this will have an impact on the hotel if this is allowed and not handled properly. Through the survey method, research was conducted by distributing questionnaires to 100 respondents, and analyzed using simple linear regression, Spearman rank correlation, and the coefficient of determination. The result is that there is an influence of service quality on guest satisfaction, and there is a positive relationship between the two variables; the independent variable contributes to the dependent variable. Although the relationship and contribution are minor.